(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The elimination of underdevelopment is relevant in modern speech therapy is one of the problems. This is of great practical importance: the speech is complete early detection of underdeveloped children and timely correction work to prevent and eliminate children’s backwardness in learning their mother tongue important in maturation. There is a number of research areas in this area conditioned by factors.